When innovation rests on sustainability and food safety: Some experiences from Italian agri-food start-ups - Del Baldo, Mara (Frontiers in Sustainability, 2022)
In the context of the agri-food industry, innovative start-ups have come into the spotlight as key drivers of innovation, sustainability and food safety orientation. Prior studies have produced significant knowledge on these topics but have mainly addressed established enterprises, while little is known about agri-food start-uppers and their contribution to social and eco-innovation. To fill this gap, this paper explores new entrepreneurial initiatives in the agri-food industry to understand how and why food safety, as well as environmental and social sustainability issues, are incorporated into their business models. The empirical analysis — based on four Italian start-ups — points out start-uppers’ awareness of the importance of protecting the environment and promoting sustainability and health. In this vein, innovation is driven by the start-upper desire to actively contribute to educate the consumer on healthier and more sustainable food and trigger more sustainable lifestyles. Accordingly, their businesses, given their agility and flexible models, are by nature among the first to propose innovative solutions that incorporate the principles of circular economy and sustainability.